Opefb Pretreatment Using The Low-cost N,N,N-dimethylbutylammonium Hydrogen Sulfate Ionic Liquid Under Varying Conditions - Shikh Mohd Shahrul Nizan Shikh Zahari; Yichen Liu; Putian Yao; Mahfuzah Samirah Ideris; Hazeeq Hazwan Azman; Jason P. Hallett (Springer Nature Limited, 2024)
Indexed by Scopus/ERA